German Finanzkapitalismus: A narrative of Deutsche Bank and its role in the German financial system - Reinhard H. Schmidt (IBF - Institut für Bank- und Finanzgeschichte, 2020)
This paper provides an account of the history of Deutsche Bank in the style of a narrative. Since more than 120 years, Deutsche Bank has been the most important German bank. Its history has been shaped by crises and efforts to overcome them. Moreover, throughout its history, the development of Deutsche Bank has been closely related to that of the German financial system, and as the paper tries to demonstrate, Deutsche Bank had a stronger influence on the character of that system than any other German institution. The paper focuses on three additional aspects of the bank's history, which have repeatedly changed over time: (1) its degree of internationalization, (2) the extent to which Deutsche Bank has focused on investment banking (as opposed to commercial banking) and (3) the consistency of its business model.
Keywords: G21; N24; 330